2021
DOI: 10.1164/rccm.202102-0509oc
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3 Open-Label Study of Elexacaftor/Tezacaftor/Ivacaftor in Children 6 through 11 Years of Age with Cystic Fibrosis and at Least One F508del Allele

Abstract: contributed equally to this article. ** Drs. Wainwright and McColley contributed equally to this article.+Associate Editor, AJRCCM (participation complies with American Thoracic Society requirements for recusal from review and decisions for authored works).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
157
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 35 publications
16
157
0
1
Order By: Relevance
“…The development and recent approval of an increasing number of CFTR modulator drugs has created an unprecedented opportunity to treat the basic defect in a growing number of patients with CF [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, clinical trials of CFTR modulators showed heterogeneous responses in clinical outcomes as well as sweat chloride concentration among patients with identical CFTR genotypes.…”
Section: Icm As Outcome Measure Of In Vivo Response To Cftr-directed Therapeuticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and recent approval of an increasing number of CFTR modulator drugs has created an unprecedented opportunity to treat the basic defect in a growing number of patients with CF [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. However, clinical trials of CFTR modulators showed heterogeneous responses in clinical outcomes as well as sweat chloride concentration among patients with identical CFTR genotypes.…”
Section: Icm As Outcome Measure Of In Vivo Response To Cftr-directed Therapeuticsmentioning
confidence: 99%
“…Recently, a triple combination of the two correctors elexacaftor and tezacaftor with the potentiator ivacaftor showed substantial clinical improvement in patients with CF with at least one F508del allele [ 10 , 11 ]. As a result, effective CFTR modulators have recently been approved and are becoming available for the treatment of approximately 90 % of CFTR genotypes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Despite this unprecedented breakthrough in precision medicine of the underlying CF defect, there are still approximately 10% of patients with CFTR genotypes that cannot be treated with current CFTR-directed therapeutics.…”
Section: Potential Use Of Icm For Personalized Medicine For Patients With Rare Mutations and High Unmet Needmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently released phase 3 data for ELX/TEZ/IVA use in children 6 to 11 years of age showed positive safety and tolerability results, as well as secondary endpoint improvements in ppFEV1, sweat chloride, Cystic Fibrosis Questionnaire-Revised (CFQ-R) scores, body mass index (BMI), as well as number of pulmonary exacerbations and hospitalizations. 1 Studies have also documented that initiating HEMT at an earlier age has the potential to alter the progression and prognosis of CF. [2][3][4] Based on this information, a supplemental New Drug Application to expand the use of ELX/TEZ/IVA to include children 6 to 11 years was submitted in early 2021 with a targeted decision date of June 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we learn the results of the Phase III clinical trial to prove safety and tolerability of ELX/TEZ/IVA in children aged 6 to 11 years (3). In this study, the open label use of ELX/TEZ/IVA was studied in 66 children.…”
mentioning
confidence: 99%